The Effect of Digital Marketing (Digital Marketing in Android Platform) on Brand Awareness on E-Commerce - Novita, Diana; Herwanto, Agus; Andriani, Jeni; Wulansari, Retno; ., Syahrul (KnE Social Sciences, 2024)
Digital marketing is no longer a new thing. This is because the ease of access to existing digital information does not limit marketing. What’s more, there are many digital marketing books and journals that can be used as references. Besides, we are living in digital era where we can access all the information whether we need it or not. Life is becoming easier with all the technologies that we have nowadays. In this research, the author explains the digital marketing that use android as its implementation. In Indonesia, there are two big online transportation apps that most Indonesian citizens use on a daily basis. They are GOJEK and GRAB BIKE. These apps also offer several facilities to small business to market their products. It is called GOFOOD and GRABFOOD. With this, GOJEK and GRAB bike have really helped small businesses to survive specially during the time of pandemic. This study aims to determine the effects of digital marketing on brand awareness. While the independent variables are Go Food (X1) and Grab Food (X2), the dependent variable is brand awareness (Y). The study uses multiple linier analysis techniques. For data collections, researches used an online questionnaire via Google Forms. The result showed that digital marketing variables using Go Food and Grab Food had a significant influence on brand awareness. Keywords: digital marketing, Android platform, brand awareness, e-commerce